The Relationship of The Media to The Spread of Social Phenomena in Society – Suicidal Thoughts, For Example - Hemin Amin Jalal Shwani; Hunar M. Hussein (QALAAI ZANIST JOURNAL, 2023)
Suicide as a social phenomenon has increasingly become a subject matter of interest to sociologists, especially the sociologists of the media. They have used various tools and theories to explain the causes and consequences of this phenomenon. Although traditionally the factors of mental disorders, anxiety, drug use, social relationships, health, economic and social pressures are taken as the main causes of suicide, today the media has also increasingly becomes an important causal factor in the spread of this phenomenon in society. This is mainly because journalists do not have a necessary level of knowledge on how to cover the stories of suicide by considering the consequences and impacts of their media handling of this phenomenon on the safety of individuals in society especially in developing countries. By analyzing the content of (126) news stories about (suicide) in (17) different news channels in Kurdistan Region of Iraq during three months, this study has found out that instead of promoting preventive measures against suicide or encouraging anti-suicide culture, the news outlets have actually become a contributing factor in the increasing rate of the phenomenon by spreading fear and hopelessness among the public. Additionally, journalists follow minimum level of the recommendations issued the World Health Organization (WHO). For example, in a survey for this research based on the guidelines of the WHO, I found out that the level of journalists’ awareness of the question of suicide stands around the weighted mean of 3.16 on average which indicates a high level of lack of awareness.